The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/nmo.12627
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis is associated with increased impedance measures of reflux compared to non‐fibrotic disease among pre‐lung transplant patients

Abstract: Abnormal reflux was significantly more prevalent among IPF patients after controlling for lung disease severity. Gastroesophageal reflux/microaspiration likely plays a role in fibrosis in IPF. A significant portion of IPF patients had increased non-acid reflux. Therapies aiming to prevent reflux of gastric contents may be more beneficial than antisecretory medications alone in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
5
24
0
1
Order By: Relevance
“…Interestingly, less than 50% of IPF patients in these studies reported classic reflux symptoms such as heartburn and regurgitation . Idiopathic pulmonary fibrosis patients also have more bolus reflux when compared to patients with non‐fibrotic lung disease of similar clinical severity, suggesting that the high prevalence of GER in IPF is not solely a function of altered respiratory mechanics, but that GER may in fact contribute to pathogenesis of the underlying lung disease.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, less than 50% of IPF patients in these studies reported classic reflux symptoms such as heartburn and regurgitation . Idiopathic pulmonary fibrosis patients also have more bolus reflux when compared to patients with non‐fibrotic lung disease of similar clinical severity, suggesting that the high prevalence of GER in IPF is not solely a function of altered respiratory mechanics, but that GER may in fact contribute to pathogenesis of the underlying lung disease.…”
Section: Discussionmentioning
confidence: 95%
“…Today, there is evidence that aspiration of gastric and esophageal contents can cause a wide spectrum of respiratory disorders, from cough to lung fibrosis. 17,18 Among 110 patients with achalasia, Sinan et al reported the occurrence of at least one daily respiratory symptom in 51 of them (40%). 3 Regurgitation was present in 100% of our patients with respiratory symptoms, with choking in the supine position in 45%, suggesting that aspiration played a role in the pathogenesis of these symptoms.…”
Section: Achalasia and Respiratory Symptomsmentioning
confidence: 98%
“…Additionally, in patients with idiopathic pulmonary fibrosis (IPF), GERD has been shown to have increased prevalence in comparison to other chronic lung diseases[46,50,51]. Gavini et al[52] demonstrated that patients with IPF undergoing pre-lung transplant evaluation have a significantly higher prevalence of abnormal reflux compared to those with COPD, after controlling for potential confounders such as underlying disease severity. Savarino et al[53] demonstrated that IPF patients had a higher total reflux episodes and total proximal reflux episodes compared to both non-IPF chronic lung disease patients and healthy volunteers.…”
Section: Gerd and Lung Disease: Significance Of The Problemmentioning
confidence: 99%